Transformational Leadership Practices with Principals Dual Roles in the Age of Education 4.0 - Al-Ghozali, Mohammad Faizal; Pabbajah, Mustaqim; Widyanti, Ratri Nurina; Widyatmoko, Widi Fajar (Pencerah, 2025)
This study aims to explore the practices of transformational leadership implemented by the principal, who concurrently holds the role of a guidance and counseling teacher at SMPN 3 Cikembar, within the context of Education 4.0. The main focus of this study is to understand how these leadership practices are implemented, the factors that support their success, and their impact on the school's readiness to face digital challenges and educational innovation in the era of 4.0. This research uses a qualitative approach with a case study method, involving the principal, teachers, and students as key informants. Data collection techniques were carried out through observation, interviews, and documentation. The results of the study show that the principal applies seven forms of transformative leadership, including modeling, inspiration, giving appreciation, supporting creativity, discussion forums, empathy for school members, and digitizing learning. The success of these practices is supported by personal commitment, a background in guidance and counseling, the ability to handle multiple tasks, and collegial support from teachers. In conclusion, humanistic-based transformative leadership can create a collaborative and adaptive school environment. This study recommends ongoing training/workshops, inter-school collaboration systems, and a humanistic approach to educational leadership to effectively address the challenges of the 4.0 era.